KOMUNITAS SASTRA JAWA: PENCIPTAAN, PENERBITAN, DAN PERGELARAN TEMBANG MACAPAT - Akhmad Nugroho (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2017)
This article is result of a research that describes tembang macapat (Javanase traditional poem) whichbelongs to the Javanese community and commonly read in a recital. The description encompasses the creative, the publishing, and the recital processes. This research is conducted by the use of descriptive qualitative method. Data is collected by participatory observation and interview, and analysed critically by the theory of tembang. Result shows that tembang macapat is one of Javanese traditional literary works. It is called traditional due to the rigid rules applied on the writing process. Rules that have to be adhered are guru gatra (number of lines on each verse), guru lagu (vocal sound at the end of each line), and guru wilangan (number of syllable on each line). These rules differ from the rules in Javanese literary works called geguritan, which is more like free poem. To date, traditional tembang or macapat is produced by Javanese and published in local newspaper. It is also recited in a performance before audiences. The performance of macapat can still be found in Yogyakarta and conducted at night. In this way tembang macapatan is preserved, well appreciated by the Javanese and becomes precious legacy.